VD_FINDINFO ML / 2013 / 129 vom 2. Mai 2013 - VD Tribunal cantonal (2013)
MAINLEVÉE DÉFINITIVE, TITRE DE MAINLEVÉE, SENTENCE ARBITRALE, DÉCISION ÉTRANGÈRE, EXÉCUTIONPROCÉDURE | 194 LDIP, 80 LP, 81 LP, 138 CPC (CH), 326 CPC (CH), 335 al. 2 CPC, 45 CDPJ